Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18157983
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Preparedness and Perceived Safety in Nursing Homes in Southern Portugal: A Cross-Sectional Survey-Based Study in the Initial Phases of the Pandemic

Abstract: (1) Background: Nursing homes’ preparedness in managing a public health emergency has been poor, with effects on safety culture. The objective of this study was to assess nursing homes’ COVID-19 preparedness in southern Portugal, including staff’s work experiences during the pandemic. (2) Methods: We used a COVID-19 preparedness checklist to be completed by management teams, followed by follow-up calls to nursing homes. Thereafter, a survey of staff was applied. Data analysis included descriptive statistics, e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…To cope with the pandemic-induced stressors, HCWs adopted various strategies, including seeking support/guidance from peers and leadership, which they felt was integral to their wellbeing. A study of 720 Portuguese LTC staff identified teamwork (78%), and staff training (70%) as key strategies to ensure staff wellbeing and a safety culture (Brito Fernandes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To cope with the pandemic-induced stressors, HCWs adopted various strategies, including seeking support/guidance from peers and leadership, which they felt was integral to their wellbeing. A study of 720 Portuguese LTC staff identified teamwork (78%), and staff training (70%) as key strategies to ensure staff wellbeing and a safety culture (Brito Fernandes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as pointed out by Ben-Ari (1996), Bartzokas and Slade (1991) Finally, due to the rapidly changing nature of emerging infectious diseases and the importance of health and care workers in their prevention, there is an urgent need to explore a more comprehensive and systematic framework for preventing these diseases in facilities. We believe subthemes 3.1, 3.2, and 3.3 on facility resources, employee quality, and management model, respectively, can serve as guidelines for establishing such a framework and reducing the barriers to preventing emerging infectious diseases in long-term care facilities as identified in previous studies (Brito Fernandes et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Nursing home uses social media to keep families informed about residents' well-being during COVID-19 pandemic (Brito Fernandes et al, 2021).…”
Section: Managing Informatics and Telehealth Devicesmentioning
confidence: 99%
See 2 more Smart Citations